Pengabdian PKM Program Perbaikan dan Edukasi Penggunaan Peralatan Audio Bagi Panti Asuhan Fachrudin Semarang - Hadi Kunaryo, Bambang; Rahmawan, Afeef Kurnia; Winasis, Ganjar; Hermana, Rifki (IRA Jurnal Pengabdian Kepada Masyarakat (IRAJPKM), 2025)
Audio equipment is an essential facility in educational institutions, including at Fachrudin Orphanage in Semarang, where it supports daily activities such as worship, learning, guidance, and social events. However, improper installation and operation have led to suboptimal audio output and equipment damage, such as a horn speaker failure caused by overpowering and incorrect cable connections. This Community Service Program (PKM) aimed to repair damaged audio equipment, improve installation, and educate users on proper operation. The methods included field surveys, damage identification, repair of equipment and wiring, and user training. The results showed that correcting the installation and providing technical education significantly improved sound quality and helped prevent further damage.